Metachronous Second Primary in the Form of Nasopharyngeal Carcinoma Following Treatment of Small Cell Neuroendocrine Carcinoma of the Head and Neck: Dual Tracer PET/CT Findings Highlighting SSTR2 Expression and Its Theranostic Implications - Edamadaka, Yeshwanth; Sonavane, Sunita Nitin; Basu, Sandip (World Journal of Nuclear Medicine, 2024)
Patients of head and neck squamous cell carcinoma (HNSCC) experience increased risk of developing second primary cancer (SPC) necessitating active surveillance during their disease course. SPCs are associated with poor prognosis and are the leading cause of long-term morbidity and mortality impacting survival of patients with HNSCC. Small cell neuroendocrine carcinoma (SmNEC) is a rare but aggressive neoplasm with poor prognosis and high risk of local recurrence and distant metastasis. We report an exceedingly rare case of nasopharyngeal carcinoma (NPC) presenting as a recurrence in the form of metachronous second primary to primary SmNEC 9 years after chemotherapy. The dual tracer positron emission tomography and computed tomography (PET/CT) imaging approach ([68Ga]Ga-DOTATATE-PET/CT with 18F-FDG-PET/CT) was explored in such metachronous NPCs, and the findings are illustrated with its potential for theranostic applications. NPC is a rare malignancy with significant geographical variations in incidence rates. Somatostatin receptor 2 (SSTR2) expression in NPC is well documented and can serve as a potential theragnostic marker in advanced NPC where the successful outcome is minimal with currently available treatment modalities.
Keywords: sinonasal carcinoma; small cell neuroendocrine carcinoma; NEC; 18F-FDG; [68Ga]Ga-DOTATATE; nasopharyngeal carcinoma; metachronous second primary malignancy